Peran Mediasi LMX terhadap Pengaruh Organizational Climate dan Trust terhadap Knowledge Sharing dalam Pengembangan Kompetensi Teknis - Marhaeni, Karantina; Ardiyanti, Niken (Jurnal Manajemen dan Usahawan Indonesia, 2020)
The purpose of this research is to examine the influence of organizational climate, trust and leader-member exchange (LMX) on knowledge sharing, as well as the mediating role of LMX on the impact of organizational climate and trust on knowledge sharing. The research was conducted on operators and technicians as participants in the accelerated competency development program in an oil and gas refinery business. This research was an applied analytical research using an empirical approach with a mixed – method data collection technique between quantitative using a questionnaire and qualitative using an open questionnaire. Data were collected from 419 respondents or represent about ten percent of the randomly selected population. Meanwhile, open questionnaires were distributed to program managers and users. Data was analysed using structural equation modeling (SEM). The findings showed that Fairness and Cognitive Trust had significant effect on knowledge sharing. Meanwhile Affiliation and CognitiveTrust did not fully had significant effect on knowledge sharing. LMX had significant influence on knowledge sharing directly, but MLX did not fully mediate the influence of organizational climate and trust on knowledge sharing. It is expected that this research could be referred by management and HR practitioners in managing knowledge, especially in the process of developing technical competencies especially in the field of oil and gas refinery business.